Structures and Systems: An approximation to the Relativized Conceptualization Method of Mioara Mugur-Schächter - Fernández Agis, Domingo (Analysis. Journal of Philosophical Research, 2019)
In this work, starting from some reflections of an epistemological nature, I propose an approach to the Relativized Conceptualization Method (MCR), as it has been proposed by the physics and epistemologist Mioara Mugur-Shächter, trying to highlight its philosophical presuppositions and its physical-matematical foundations. Next, I intend to show the basics guidelines that govern its applicability, thus evidencing its practical interest.